Algorithm for the Min-Max problem of an optimal control - AIDENE, M; OUKACHA, B (Sciences & Technology. A, exactes sciences, 2004)
In this paper, we consider an optimal control non linear problme with bounded constraints on reachability set. The interest of this problem is the Min-Max model who has several practical applications and the method of resolution. The first generalizations of this method to the Min-Max is linear programming and in optimal control are presented in the results [6-10]. The method proposed [1-3] in this paper is a generalization to the problem with a bounded goal set.